Labour supply and income distribution effects of the working income tax benefit: A general equilibrium microsimulation analysis - Nabil Annabi; Youssef Boudribila; Simon Harvey (IZA Journal of Labor Policy, 2013)
In this study we assess the impact of the Working Income Tax Benefit (WITB) on labour supply, GDP and income distribution in Canada, using a general equilibrium microsimulation model. We also estimate labour supply and demand elasticities using survey data to ensure that households' behaviour is properly captured in the model. Simulation results show that the WITB affects particularly labour market participation of low- and medium-skilled lone-parents families. These positive effects on labour supply translate into higher after-tax incomes leading to a decline in low-income rates and low-income gaps. Our findings suggest that enhancing the WITB could provide additional income support to working Canadian families while reducing work disincentives for those trapped behind the welfare wall.
Keywords: C15; D33; D58; J08; I32; O51; 330; general equilibrium; microsimulation; elasticities; labour supply; income distribution; Canada